Analysis of Multiple Representation Ability of Chemistry Education Students on Hydrocarbon - Ichsan, Rizki Furqanul; Enawaty, Eny; Erlina (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to analyze students’ multiple representation ability on hydrocarbon which includes macroscopic, submicroscopic, and symbolic representations. The research subjects were Chemistry Education Study Program students of FKIP Tanjungpura University class of 2022 and 2023 who had taken the Organic Chemistry of Monofunctional Compounds course, totaling 108 people. The research used a quantitative descriptive method with an instrument in the form of a description test of 9 questions, each of which represented three levels of representation. The results showed that students’ macroscopic representation ability was classified as good with an average of 68.30% (batch 2023) and 64.86% (batch 2022). The submicroscopic representation ability is classified as good, with an average of 70.26% (batch 2023) and 69.59% (batch 2022). Meanwhile, the symbolic ability of the 2023 batch students was classified as sufficient with an average of 53.43%, and the 2022 batch was classified as good with an average of 67.10%. These findings indicate that students still experience difficulties, particularly in mastering symbolic representation, which is a crucial aspect in understanding hydrocarbon chemistry concepts. Therefore, training in symbolic representation mastery is necessary. The novelty of this research lies in the focus of the analysis of students’ abilities in integrating the three levels of representation comprehensively on the topic of hydrocarbons, which until now has rarely been studied specifically in the context of chemistry education.